"Thinking with my dad brain, not my man brain": Understanding Men's and Women's sterilization risk narratives. (January 2022) - Kissling, Alexandra
Abstract: The interpretation of risk influences women's reproductive decisions. Research has yet to show how men understand and interpret risk, particularly in their decision to use contraception. Contraceptive sterilization provides a case through which we compare risk narratives between men and women, as it is the only analogous birth control for both men and women. A study of risk narratives held by sterilized adults and their partners reveals how risk narratives are gendered and how they contribute to contraceptive use. Using 75 in-depth interviews with sterilized heterosexual men (n = 25), women (n = 25), and unsterilized partners (n = 17 women, n = 8 men), the present study finds that men and women report similar risk narratives grounded in (1) birth control risks to health and life plans and (2) risks to maternal health from past pregnancies and age. As expected, women's risk narratives appear to stem from their embodied experiences and their interactions with medical authorities. Rather than addressing their own embodied experiences or experiences with medicine, men's beliefs mirror women's, and are centered on the dangers of hormonal birth control and pregnancy to women. This study is novel in showing the couple dyad as a site of men's beliefs about risk, as how heterosexual couples form ideas about health and life plan risk through a mutually shared gendered lens. Highlights: Sterilized adults and partners report risk narratives from birth control and maternal health. Men and women alike report risk narratives focused on women's bodies. Men's risk narratives come from couple dyads, wherein they adopt the beliefs of their women partners.